Effect of fiber densities on impact properties of biaxial warp-knitted textile composites. (August 2015) - Demircan, O; Yilmaz, C; Kocaman, ES; Tang, S; Hamada, H; Yildiz, M
In this study, an appropriate fabric weight content controlled by the density of the warp and weft fibers is determined for biaxial warp-knitted composites referring to mechanical test results. Six different types of composite panel with two different fabric weights (813 and 1187 gr/m 2 ) and with three different stacking sequences [90we /0wa /90we /0wa ]s, [90wa /0we /90wa /0we ]s, and [90wa /0we /90we /0wa ]s are fabricated by using Resin Transfer Molding method. Having produced composite panels, drop weight impact tests are conducted on specimens. Microstructural characterization of impact tested materials is performed using optical microscope. The results of this study reveal that composites with biaxial warp-knitted preforms with lower weft and warp fiber densities (thin-ply) could absorb higher impact energies compared to those with higher weft and warp fiber densities (thick-ply).